1971
DOI: 10.1121/1.1912511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic Vibration on Coefficient of Friction during Strip Drawing

Abstract: Effect of ultrasonic vibration on coefficient of friction between a rigid steel die and plastically deformed metal has been studied. The coefficient of friction was measured during a strip-drawing operation with and without application of ultrasonic vibration. The application of ultrasonic vibration during the drawing process substantially reduces the coefficient of friction and die stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 0 publications
1
12
0
2
Order By: Relevance
“…The advantage of conducting ultrasonic tension tests, rather than just ultrasonic compression tests, in this investigation is that the effects of contact, in particular friction effects, are eliminated. Hence, the measured reduction in the maximum oscillatory stress cannot be attributed only to contact conditions as suggested in some previous studies [13,18,19].…”
Section: Tension Test Stress-strain Datamentioning
confidence: 57%
See 1 more Smart Citation
“…The advantage of conducting ultrasonic tension tests, rather than just ultrasonic compression tests, in this investigation is that the effects of contact, in particular friction effects, are eliminated. Hence, the measured reduction in the maximum oscillatory stress cannot be attributed only to contact conditions as suggested in some previous studies [13,18,19].…”
Section: Tension Test Stress-strain Datamentioning
confidence: 57%
“…This explanation has often been rebuffed in the literature [2,8,15], partly because it is known that there is no significant increase in specimen bulk temperature during ultrasonic compression tests, and also because it is known that significant absorption of ultrasonic waves to cause resonance of dislocations can only occur at 100 MHz frequencies and not in the low kHz ultrasonic range [19]. However, it is clear from the experimental data, that neither the tension or compression tests satisfy the description of stress superposition and, since there is no contact friction effect in the tension test data, the effects of a temporary change in materials properties is investigated, first for the tension test FE model and then for the compression test model.…”
Section: Adjusting Materials Propertiesmentioning
confidence: 93%
“…Many early investigations reported that by superimposing an ultrasonic excitation on the static load during plastic deformation, the flow stress was reduced. This reduction in flow stress in ultrasonic metal working was attributed to several phenomena including dynamic effects of high frequency vibrated tools, alterations in material properties, local increases in temperature and changes to the interface friction condition [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…For the metal drawing process a reduction in drawing and die forces was observed. Static friction forces subject to vibrations are reduced and a change in elastoplastic deformation of the contact in a static friction joint is observed [5]. Another investigation in plastic forming showed that ultrasonic oscillations apply additional acoustic stress that affects friction resulting in lower drawing forces [6].…”
Section: Introductionmentioning
confidence: 99%
“…Rozner et al [5] showed that ultrasonic vibration effects the friction forces between metals in strip drawing. For the metal drawing process a reduction in drawing and die forces was observed.…”
Section: Introductionmentioning
confidence: 99%